Amplitude-phase modulation metasurface hologram with inverse angular spectrum diffraction theory. (9th June 2022) - Su, Deer; Wang, Xinwei; Shang, Guanyu; Ding, Xumin; Burokur, Shah Nawaz; Liu, Jian; Li, Haoyu
Abstract: Designed metasurfaces, composed of a two-dimensional array of meta-atoms, provide an alternative approach to achieving efficient electromagnetic wave manipulation. Metasurface holography is an emerging and promising imaging technology, with improved image quality and spatial resolution compared to traditional holography. Many devices are fabricated only by coding specific phase responses of the designed metasurfaces. However, the modulation of both the amplitude and phase responses of electromagnetic waves can significantly improve the quality of the holographic image. In this paper, we employ bi-layered split rings as meta-atoms, which can fully control the transmission amplitude and phase independently. Furthermore, we present an algorithm based on the inverse angular spectrum diffraction theory to obtain the amplitude and phase information for the shape and arrangement of the meta-atoms. The proof-of-concept experiments in the microwave regime demonstrate that the inverse angular spectrum diffraction theory shows better image quality than the conventional Gerchberg-Saxton algorithm, especially when the number of meta-atoms is the same or even slightly fewer. The proposed approach provides an innovative and effective method for hologram design and expands the route to versatile applications related to holographic technologies.